Polymerization shrinkage stress of contemporary dental composites: Comparison of two measurement methods - Szczesio-Wlodarczyk, Agata (Japanese Society for Dental Materials and Devices, 2025)
The aim of this study was to compare two testing methodologies employed for assessing the polymerization shrinkage stress of dental resin composites. Ten commercial resin composites were investigated (EverX Posterior & Flow; G-ænial Anterior, Posterior, A'CHORD & Universal Injectable; Filtek One Bulk Fill & Universal Restorative; SDR flow+ and Aura Bulk Fill). Photoelastic and contraction forces measurement methods were performed. The slope of the linear trendline and C-factor of specimens were calculated. The shrinkage stress values (range between: 6.4-13.4 MPa) obtained by the photoelastic method were higher for all resin composites than the values obtained by contraction forces measurements (range between 1.2-4.8 MPa). However, there was a strong linear correlation between these methods (r=0.8). The use of both investigated methods revealed important information about the shrinkage behavior of the restorative resin composites.